Modern approaches to the rationing of managerial labor (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Article deals with the modern management problem associated with improving the accuracy of the ration of managerial work. Emphasis is on the need to move from the rationing of the working day to the rationing of individual labor functions (operations). The subject of the article is contradictions arising in the process of integration of quantitative and qualitative methods of research of the work process. The main purpose of the article is to create the author's concept of overcoming contradictions between the existing methods of regulation managerial labor and the practical need of enterprises in developing these norms. Concept is based on the synthesis of quantitative and qualitative methods. The methodological framework of the study consists of the concept of foreign and domestic researchers involved in the issues of labor rationing and management efficiency. The problem of the article lies in the fact that the existing approaches to standards of management personnel are not sufficiently adapted to solving problems in conditions of intellectual labor. The cause of the problem is seen as the need of enterprises to improve the efficiency of not individual employees involved in management issues, but of the entire business process management. In combination with the totality of such general scientific and special methods of cognition, such as dialectical, systemic, descriptive, theoretical modeling, the article offers approaches to eliminate this contradiction. The main conclusion of the article is the necessity of application of two-stage approaches to the valuation of managerial work, where the first phase involves a qualitative analysis of the structure of the business process, is conducted after the close study of the cost of labor in the performance of these functions. The article defines the limitations of the application of this method and offers recommendations for its integration with methods of studying the cost of working time. As the resulting conclusions, it is proposed to apply not for all business processes but for the most significant for the organization. This method will optimize the costs of rationing, and explore only the largest (and, accordingly, costly) business processes for an organization. The basis of this method is the ranking system proposed in the article. It is also insisted that in modern management practice it is inappropriate to control individual participants in a business process (jobs). It is necessary to standardize the entire business process with its further distribution among the performers.